(untitled) (Medico Legal Update, 2021)
Virtual autopsy is a specialized technique of postmortem examination where in radiological imaging techniques are used to scan body of dead to make opinion regarding cause of death and other valuables. It is performed independently or with traditional autopsy. There are numerous advantages of this technique over traditional autopsy. Due to technical and organizational problem, virtual autopsy service is not commonly in use in developing countries. In our study we have collected responses of medical professionals through questionnaires based on virtual autopsy facts, techniques, advantage, and disadvantage in comparison to traditional autopsy (TA). Results are heartening to know that most of the participants are well aware of the fact of our study objectives but more awareness is needed to promote this important aspect of medicolegal and forensic medicine practice to minimize time, energy and risk due to COVID 19 pandemic and other factors.